The treatment of hyperphagia and obesity in Prader-Willi Syndrome - Ilona Jastrzębska; Paulina Cuper; Michał Andrzej Kozicz; Krzysztof Bilecki; Hubert Gugulski; Michał Bado; Patrycja Nowoświat (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Prader-Willi Syndrome (PWS) is a genetic neurodevelopmental disorder, in which the central clinical characteristics are hyperphagia and obesity. Obesity leads to higher mortality rates in PWS patients and thus, effective and safe treatment of hyperphagia and obesity in PWS individuals is an important aspect of PWS therapy. Aim of the study: The aim of the study was to research both the new and the more standard treatment options of hyperphagia and obesity in PWS patients. Methods and Materials: An extensive literature search was conducted using PubMed database. Only articles from the past 5 years were taken into consideration. The keywords used during the search were: prader willi syndrome, obesity, treatment. Results: Our research showed that in the treatment of hyperphagia and obesity in PWS patients, health professionals may consider the use of pharmacological treatment options, surgery and neuromodulatory options. Moreover, physical activity and environmental control are beneficial in limiting caloric intake and improving body mass index. Furthermore, early diagnosis and thus starting treatment in early childhood are beneficial in preventing the progression of obesity. However, more research is needed to determine which treatment options are best suited for specific patients.